(untitled) (Sustainability in Debate, 2016)
This article seeks to analyze the methodological approaches in the determination of biodiversity offsets required to maintain and create protected areas in the states of Amazonas, Bahia, Mato Grosso do Sul, Paraná and Rio de Janeiro. The study followed a qualitative and descriptive approach. Data were collected through academic and grey literature reviews. Three Brazilian states were found to have unique approaches for estimating biodiversity offsets; two states still use the generic national-level approach. The states with unique offset methodologies are able to capture, in more detail, ecosystem components, and are thus potentially more precise in determining significant impacts. None of the approaches were found to be able to estimate the impacts that can be mitigated and restored, which is in conflict with the theoretical principles of biodiversity offset calculation. The article concludes with a recommendation for future lines of research on the matter.